Erasmus – AI Chatbot - Thakkar, Jash; Raut, Purva; Doshi, Yash; Parekh, Krishma (International Journal of Computer Sciences and Engineering, 2025)
ERASMUS is a chat bot on Facebook which is used to answer the queries related to the college information in one go. There has been an increasing demand for Chatbots on the websites of colleges or Educational Institutes. The college websites are generally unmaintained and filled with redundant information. Finding the required information on the website becomes a tedious task for students, teachers, parents or other users. The problem also gains a boost during time of admission, as the requirement for information increases during that time. A chatbot on the college website will help the users find the required information in a few clicks and questions. The chat bot detects the intent of the queries received from the users and accordingly parses the website to find the related information. There is no specific format the user must follow. The system uses built in artificial intelligence to answer the queries. The user can query any college related activities through the system. The user does not have to personally go to the college website for any enquiry.